Christian theology and the new atheism: the hierarchy of explanations - Nonyelu, Francis (Teologia w Polsce, 2020)
The hierarchy of explanations is necessary. Both science and theology are rooted, each in its own way, in the human desire to understand and know, but they seek understanding and truth from within formally distinct horizons of inquiry. These horizons do not overlap, compete, or conflict with each other, and what constitutes data, evidence, and confirmation in one is not the same as in the other.